PERAN PTKI DALAM MEMBANGUN AKHLAK DIGITAL PADA GENERASI MEDIA SOSIAL: STUDI LITERATUR DAN ANALISIS KONSEPTUAL: The Role Of Ptki In Developing Digital Character In The Social Media Generation: Literature Study And Conceptual Analysis - Mutamakin; Rif'an, Ali; Said, Akhmad (Piwulang: Jurnal Pendidikan Agama Islam, 2025)
This study examines the strategic role of Indonesian Islamic Religious Higher Education (Perguruan Tinggi Keagamaan Islam/PTKI) in fostering digital ethics (akhlak digital) among the social media generation. The rapid digitalization in Indonesia has created a paradox: while offering unprecedented connectivity, it also exacerbates moral crises such as the spread of hoaxes, hate speech, and cyberbullying. This research argues that PTKI, with its dual mission of developing intellect and character, is uniquely positioned to address this gap. Through a systematic review and conceptual analysis of relevant literature, this study constructs a framework of akhlak digital by contextualizing classical Islamic ethical values (e.g., shiddiq, amanah) into the digital realm. The findings map PTKI's potential roles across three domains: curricular (integrating ethics into courses), co-curricular (training and campaigns), and institutional (policy and culture). The study also identifies key internal and external challenges to implementation. This research concludes that PTKI must adopt a holistic and multi-strategy approach to effectively build digital character, offering both a theoretical contribution to Islamic education and practical recommendations for educators and policymakers.